UJI MUTU CRUDE PALM OIL (CPO) HASIL PRODUKSI PT. X DENGAN METODE SQC (STATISTICAL QUALITY CONTROL) - Desniorita, Desniorita; Ulum, Miftahul (Politeknik ATI Padang, 2017)
CPO (Crude Palm Oil) is yellow-colored crude palm oil derived from the extraction or forging of palm fruit flesh. Factors that determine the quality of CPO production are the levels of free fatty acids, moisture content, levels of impurities. The purpose of the analysis is to analyze how big the deviation of quality of CPO that is free fatty acid content, water content and dirt level by using control chart chart mean (X) and control chart range (R), identify the cause of problem (deviation) of quality of CPO with a causal diagram (fishbone), and provide suggestions for improvement to improve the quality of CPO that occurred. Results obtained from 28 samples were the number of samples outside the control limit for ALB levels of 12 samples with percentage of 43%, water content of 10 samples with percentage 36%, and dirt level that is 6 samples with percentage 21%. The most influential cause when viewed with the fishbone diagram of raw material, machinery and human factors. From the analysis results can be concluded that the quality of CPO production PT X produced there is still data outside the control limit. The quality of CPO produced is influenced by raw material, human and machine factors.